Natural phytochemicals as small-molecule proprotein convertase subtilisin/kexin type 9 inhibitors - Je-Wen Liou; Pei-Yi Chen; Wan-Yun Gao; Jui-Hung Yen (Tzu Chi Medical Journal)
A decrease in the levels of low-density lipoprotein receptors (LDLRs) leads to the accumulation of LDL cholesterol (LDL-C) in the bloodstream, resulting in hypercholesterolemia and atherosclerotic cardiovascular diseases. Increasing the expression level or inducing the activity of LDLR in hepatocytes can effectively control hypercholesterolemia. Proprotein convertase subtilisin/kexin type 9 (PCSK9) protein, primarily produced in the liver, promotes the degradation of LDLR. Inhibiting the expression and/or function of PCSK9 can increase the levels of LDLR on the surface of hepatocytes and promote LDL-C clearance from the plasma. Thus, targeting PCSK9 represents a new strategy for developing preventive and therapeutic interventions for hypercholesterolemia. Currently, monoclonal antibodies are used as PCSK9 inhibitors in clinical practice. However, the need for oral and affordable anti-PCSK9 medications limits the perspective of choosing PCSK9 inhibitors for clinical usage. Emerging research reports have demonstrated that natural phytochemicals have efficacy in maintaining cholesterol stability and regulating lipid metabolism. Developing novel natural phytochemical PCSK9 inhibitors can serve as a starting point for developing small-molecule drugs to reduce plasma LDL-C levels in patients. In this review, we summarize the current literature on the critical role of PCSK9 in controlling LDLR degradation and hypercholesterolemia, and we discuss the results of studies attempting to develop PCSK9 inhibitors, with an emphasis on the inhibitory effects of natural phytochemicals on PCSK9. Furthermore, we provide insight into the mechanisms of action by which the reported phytochemicals exert their potential PCSK9 inhibitory effects against hypercholesterolemia.